Hospitalizations and mortality form otorhinolaryngologic surgeries in Brazilian states from 2011 to 2021 (Research, Society and Development, 2021)
Surgical procedures in otolaryngology have a high demand, with most of these surgeries concentrated in the Southeast region. In addition, these procedures have a high rate of cancellations and delays, causing waiting lines, these factors cause in different ways, an increase in the morbidity and mortality rate of these individuals. This study aims to assess the rate of surgical hospitalizations and mortality in otolaryngology services in Brazil, from 2011 to 2021. This is a quantitative, cross-sectional and retrospective study with data from the SUS hospital information system on admissions and mortality rate from otorhinolaryngological procedures in the period from March 2011 to March 2021. The main variables refer to hospitalizations, mortality, socioeconomic and demographic conditions (GINI and HDI). For data analysis, with a significance level of 95% (p